Preparation of cuprous‐oxide nanoparticles using ascorbic acid as reducing agent and its photocatalytic activity - Du, Dang Xuan; Anh, Pham Thi Giang (Hue University Journal of Science: Natural Science, 2019)
In this present paper, cuprous‐oxide (Cu2O) nanoparticles were successfully fabricated using ascorbic acid as a reducing agent. The purity and characteristics of Cu2O nanoparticles were determined with XRD and FT‐IR techniques. The orphology and particle size of the material were characterized using SEM and TEM, respectively. The results show that the concentration of sodium hydroxide affects the morphology and particle size of the material. Furthermore, the Cu2O nanoparticles with a particle size of 70–80 nm exhibit good photocatalytic activity on photodegradation of Rhodamine B under visible light, and the photocatalytic degradation ratio of Rhodamine B is 70%.